2019
DOI: 10.1002/ptr.6492
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of celery (Apium graveolens) on metabolic syndrome: A review of the existing evidences

Abstract: The metabolic syndrome (MetS) is a cluster of multiple conditions that includes hypertension, dyslipidemia, abdominal obesity, and hyperglycemia disorders. Most studies revealed that the MetS is accompanied with an increased risk for cardiovascular disease, Type 2 diabetes mellitus, and insulin resistance. It can be said that, in treating or preventing the MetS and its components, lifestyle adjustment and weight loss have a vital role. According to various studies, among natural compounds, celery (Apium graveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 78 publications
0
36
1
1
Order By: Relevance
“…Compared to other parts of the plant, celery seeds have more effective ingredients (Moghadam et al, 2013;Popović et al, 2006). The celery seeds contain various active ingredients, including luteolin, d-limonene, phthalides, apigenin, hesperitin, rosmarinic acid, linalool, and quercetrin (Hedayati et al, 2019;Priecina and Karklina, 2014;Tashakori-Sabzevar, Razavi, et al, 2016). The pharmacological mechanisms of these active ingredients are discovered and reported in previous studies (Anjos et al, 2013;Dianat et al, 2015;Su et al, 2015;Triyono et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Compared to other parts of the plant, celery seeds have more effective ingredients (Moghadam et al, 2013;Popović et al, 2006). The celery seeds contain various active ingredients, including luteolin, d-limonene, phthalides, apigenin, hesperitin, rosmarinic acid, linalool, and quercetrin (Hedayati et al, 2019;Priecina and Karklina, 2014;Tashakori-Sabzevar, Razavi, et al, 2016). The pharmacological mechanisms of these active ingredients are discovered and reported in previous studies (Anjos et al, 2013;Dianat et al, 2015;Su et al, 2015;Triyono et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…Common herbal remedies for the treatment of T2DM among Latinx individuals include prickly pear cactus, aloe vera, celery, and chayote [ 69 ]. The efficacy of these herbal remedies has been shown, but with uncertain implications for clinical practice; for example, while prickly pear cactus has been shown to reduce serum glucose and insulin levels, likely due to its high fiber contents and hypoglycemic properties [ 70 ], aloe vera has shown to slightly improve glycemic control, but with great heterogeneity across studies [ 71 ], substances like celery have mostly shown promise for hyperglycemia control in rat models [ 72 ]. One study found that while nearly 70% of Latinx patients used herbal remedies, a majority reported that they did not disclose their use of herbal remedies to providers [ 69 ].…”
Section: Reviewmentioning
confidence: 99%
“…Compared to other parts of the plant, celery seeds have more effective ingredients [12,13]. The celery seeds contain various active ingredients, including luteolin, d-limonene, phthalides, apigenin, hesperitin, rosmarinic acid, linalool, and quercetrin [14][15][16]. The pharmacological mechanisms of these active ingredients are discovered and reported in previous studies [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%